A Review of the Satire and Remonstrant Satire-Processing in the Poems by Sayed Hasan Hosseini with an Emphasis on the Collections "Safar Nameh Gerdbad, Boradeha and Noushdaruy-e-Tarhe-Generic" - Salimi, Hossein (2021)
Sayed Hasan Hosseini is amongst the successful and innovative contemporary poets; his poetical themes and subjects predominantly serve the expression and delineation of the people and the community’s pains and problems. Due to the same reason, he chooses satire for expressing his social thoughts in various periods of his practicing of poetry and it is by doing so that he not only criticizes and corrects the social abnormalities but he also invites the society and the people to ponder and think. In the poems by Sayed Hasan Hosseini, poetry is not only seen in the single elements and words but also in the level of sentences and themes, as well. Social evolutions and the people’s lack of adherence to the revolutionary and Islamic values can be enumerated amongst the most important reasons of satire’s presence in Hosseini’s poems. The poet’s imagination and meticulousness subject to the effect of Indian style has also caused the entering of a caustic and serious satire in his poems making them have eloquence and artistic value as well as a sort of audience-adorned sincerity. The subjects of his satires substantially contain social criticism occasionally interlaced in some of the cases with the historical and religious incidents. The present article uses a descriptive-analytical method to investigate the satire-creation methods and satirical subjects in the poems b Sayed Hasan Hosseini with an emphasis on three poetical collections by him, namely “Safarnameye Gerdbad”, “Boradeha”, and “Noushdaruy-e-Tarhe-Generic”.